Epitaxial ZnO Nanowire‐on‐Nanoplate Structures as Efficient and Transferable Field Emitters. (29th July 2013) - Song, Jizhong; Kulinich, Sergei A.; Yan, Jian; Li, Zhigang; He, Jianping; Kan, Caixia; Zeng, Haibo
<x xml:space="preserve">Abstract</x> Highly epitaxial ZnO nanowire‐on‐nanoplate structures as efficient and transferable electron field emitters are reported here. Well‐faceted ZnO nanoplates can be used as efficient substrates for the epitaxial growth of nanowires with a sharp and high‐quality interface, which significantly improves its field emitter performance. Because of its scalable preparation, high performance and facile transfer, the novel material is of high potential for applications in various optoelectronic devices. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>